2017
DOI: 10.2174/1381612823666170220163219
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Gastrointestinal Tract and Stable Gastric Pentadecapeptide BPC 157. Finally, do we have a Solution?

Abstract: Selye's syndrome produced by diverse nocuous agents and "response to damage as such" means Selye's stress triad in stress coping response to reestablish homeostasis. Logically, from the gastrointestinal tract viewpoint, such organoprotective/healing response implies the angiogenic growth factors that commonly signify the healing. Thereby, the gastric pentadecapeptide BPC 157-organoprotection (huge range of beneficial effects) signifies the Selye's stress concept/stress coping response implemented in and from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
200
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(200 citation statements)
references
References 0 publications
0
200
0
Order By: Relevance
“…Finally, the conclusive prospect (i.e., BPC 157 application as an innate treatment to successfully oppose invasion with N. ceranae ) is supported by a variety of beneficial effects of BPC 157 noted in colitis lesion studies (Klicek et al., ; Lojo et al., ; Sikiric et al., ; Veljaca et al., ). As indicated previously, BPC 157 has been tested in clinical trials as an agent against ulcerative colitis, but studies have shown its efficacy throughout complete gastrointestinal tract (Sikiric et al., ). BPC 157 reduces high myeloperoxidase (MPO) activity in colonic tissue (Veljaca et al., ), and in particular, heals fistulas (Baric et al., ; Grgic et al., ; Klicek et al., ), rescues failed anastomosis healing (Klicek et al., ; Sever et al., ; Vuksic et al., ), and markedly improves intestinal adaptation following massive bowel resection (Sever et al., ).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Finally, the conclusive prospect (i.e., BPC 157 application as an innate treatment to successfully oppose invasion with N. ceranae ) is supported by a variety of beneficial effects of BPC 157 noted in colitis lesion studies (Klicek et al., ; Lojo et al., ; Sikiric et al., ; Veljaca et al., ). As indicated previously, BPC 157 has been tested in clinical trials as an agent against ulcerative colitis, but studies have shown its efficacy throughout complete gastrointestinal tract (Sikiric et al., ). BPC 157 reduces high myeloperoxidase (MPO) activity in colonic tissue (Veljaca et al., ), and in particular, heals fistulas (Baric et al., ; Grgic et al., ; Klicek et al., ), rescues failed anastomosis healing (Klicek et al., ; Sever et al., ; Vuksic et al., ), and markedly improves intestinal adaptation following massive bowel resection (Sever et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…The efficacy of BPC157 (Sikiric et al., , , , ; Sikiric et al., ) in reducing N. ceranae spores number in the honeybee midgut over a short period of time and suggestion that it may limit the mortality rate in honeybees and be beneficial in nosemosis type C treatment should be validated respecting particular detrimental conditions in 2014 active honeybee season (Table ), particularly favoring invasion with N. ceranae . There were more days with rain, very low average year air temperatures, alongside with mild winter, very early honeybee brood development, increasing of V. destructor mite population (Zorat, ), decreasing the immunological status of the colonies and stress caused by hunger (lack of natural food in environment).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations